UIN Syarif Hidayatullah Jakarta USABILITY EVALUATION OF SATUSEHAT APPLICATION USING USABILITY TESTING METHOD: Analisis Keefektifan dan Kepuasan Pengguna Aplikasi SatuSehat melalui Metode Pengujian Kebergunaan - Faiz Rizki Saputra; Nia Kumaladewi (JURNAL PERANGKAT LUNAK, 2023)
SatuSehat is an application created and developed by the government of the Republic of Indonesia with the aim of controlling and tracking the spread of Coronavirus Disease (Covid-19). SatuSehat application has a main feature, namely location tracking, which requires community participation as users to report each other's locations when they travel. This aims to track the location and history of contact with people with Covid-19. However, in its use and implementation, users face various problems such as slow and difficult to understand application responses, unclear information, and frequent application problems that suddenly close. This research was conducted to evaluate the usability value of the SatuSehat application. The research method used was the SUS method by giving a questionnaire consisting of 10 questions related to the SatuSehat application to 38 respondents in the initial study. Based on this research, 7 improvement recommendations were obtained which were then implemented in the SatuSehat application. The final result shows an average value of 61.7 (Grade D). After calculating the usability value of each respondent, the final result is 61.7 (Grade D).